Digitization of Elementary School Science Learning In The Industrial Era 4.0 - Ulyawati Ulyawati; Sugito Sugito (AL-ISHLAH: Jurnal Pendidikan, 2022)
Facing this era of globalization, motivation alone is not enough, but there must be a concrete form and a hard effort. One of them is the use of technology, as for subjects related to technology, namely Science. This is because it has aspects of product, process, scientific attitude, and application. In the application aspect is the application of abstract concepts in concrete form in the form of technology. So that it leads to the development and utilization of technology with the aim of improving 4C skills. However, in reality there is still little research that explains how to digitize elementary science learning in the industrial era 4.0. So the purpose of this research is to provide an overview of digital-based elementary science learning innovations in the industrial revolution 4.0 era, in the form of strategies, media and assessment of elementary science learning. Then this research uses the literature study method, while the results of this study describe the effective digitization of elementary science learning using E-learning, personalized learning, flexible delivery, practical application, flexible exams, student ownership, and continuous feedback mechanisms. So that the researchers provide further research recommendations to describe the digitalization of science learning more broadly, including the curriculum to digital devices, as a support for the implementation of elementary science learning in the industrial era 4.0.